Boy Abunda's myth as presented in the Bear Brand "Laki sa Gatas" commercial a semiotics analysis - Tegelan, April Dawn Federizo- (2012)
"This study discussed the myths created and propagated by the Bear Brand "Laki sa Gatas" commercial and how it reinforced dominant societal codes. The study was chosen because it condensed the life of Boy Abunda in thirty (30) seconds, and used it in order to sell a commercial product. This thesis analyzed the signs present in the commercial using semiotics as lens. A discussion on the denotative and connotative meanings found in the frames of the text follows. The results gathered was analyzed and synthesized to determine the myths created by the commercial. The findings of the study support Adorno and Horkheimer' theory on the Culture Industry. This theory implies that Boy Abunda is a celebrity endorser, and therefore his life story is a commodity that can be used to sustain a capitalist system."
Vita.
Thesis (A. B. in Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Boy Abunda; Television commercials -- Philippines--Semiotics.